Training ‘leader as coach’ for direct supervisors in hospitals - Andi Indahwaty AS; Nur Arifah; Muhammad Rachmat; Ummu Kalsum (Community Empowerment, 2023)
Coaching is a process to assist employees in clarifying career goals, dealing with potential problems at work and improving employee performance. The performance of the Batara Siang Hospital in Pangkep Regency was low. It was reflected from the number of Outpatient and Inpatient visits during 2017-2020 has been decreased. In 2019, the data revealed that 4 (four) service elements were low from the community. As one of the efforts to improve hospital performance through improving human resources (HR) performance. The performance of HR is determined how their leader manage the staff. A new approach to management is needed in which leaders function as a coach for their subordinates. Therefore, the aims of this community service program are to conduct training for all level of managers regarding how to be a coach at Batara Siang Hospital, Pangkep Regency. The training participants were 35 managers. The method used is the provision of education in the form of lectures, discussions, and simulations. The evaluation results showed that there were differences in participants' knowledge between before and after participating in the training. It is hoped that the training participants will be able to provide guidance to their subordinates in the hospital so that it can have an impact on improving hospital performance.